Co-training in the field of teaching practices: meanings of a role under construction. Who are my Others in the investigation? (Praxis Educativa, 2023)
In this presentation I expose some of the advances of a research carried out within the framework of the Master's Degree in Teaching in Higher Education. I investigate the meanings that the teachers of the associated schools construct about the role of co-trainer that they officiate in the Pedagogical Residence of the Teachers of Initial Education and Primary Education in a Higher Institute of Teacher Training in the province of La Pampa. My objective is to know and interpret the meanings that the faculty of the associated school give to the role of co-trainer who carries out the training of the Pedagogical Residence student during the pandemic. For this I adopt the clinical approach, typical of ideographic sciences. Here I also express some reflections that (me) were (con)moving about who the other is in the research itself.
Keywords: teacher training, co-training, senses, clinical approach, otherness